《送你一朵小红花》影片中的修辞手法分析 PENGGUNAAN GAYA BAHASA PADA FILM “A LITTLE RED FLOWER” - Alwiyah Rahmatika; Jocelyn Johan (Journal of Language, Literature and Teaching, 2022)
Rhetoric is a way of expressing ideas through language, using language effectively. This paper takes "Send You a Little Red Flower" as the research object. The purpose of this research is to analyze the rhetorical devices used in the movie "Send You a Little Red Flower" and find out the application factors of rhetoric. According to the theory of rhetoric as the theoretical basis, this paper uses qualitative research and literature method for research and investigation. The results of the study show that there are 12 types of rhetorical devices in the film, namely: metaphor, analogy, borrowing, exaggeration, rhetorical questioning, parallelism, contrast, repetition, questioning, duality, loopback, and layering, among which repetition accounts for the most important. The application factors of using rhetoric include objective and subjective factors that affect the script of the film, making the language expression of the film more vivid and vivid, highlighting the image of the characters, and emphasizing a certain emotion of the speaker.Key words：rhetoric; film; "Send You a Little Red Flower"